Counseling on febrile seizures in the group of mothers under five in Kedungwuni District, Pekalongan Regency - Rofiqoh, Siti; Pratiwi, Yuni Sandra; Hidayati, Naela (Universitas Muhammadiyah Magelang, 2021)
Febrile seizure is a neurological disease in children that worries parents. This community service activity aims to improve parents' knowledge and skills about febrile seizures properly. The activity was carried out in groups of mothers under five in Proto and Salak Brojo Villages, Kedungwuni Pekalongan District by providing health education about febrile seizures followed by discussions and questions and answers. The results of the activity showed an increase in the average score of mother's knowledges about understanding, triggering factors, prognosis, complications, prevention and management of febrile seizures where before education was 6.7 and after education was 8.4.